Approach for an Analytical Description of the Failure Evolution of Continuous Steel and Carbon Fiber Hybrid Composites. Issue 6 (11th September 2018) - Rehra, Jan; Hannemann, Benedikt; Schmeer, Sebastian; Hausmann, Joachim; Breuer, Ulf P.
Abstract : The integration of ductile continuous steel fibers into thermoset carbon fiber reinforced polymer (CFRP) enables significant enhancements of its damage tolerance and crashworthiness. Due to their high strain at failure, the embedded steel fibers provide alternative load paths after failure of the brittle carbon fibers. The resulting post damage performance of the hybrid composite depends on the proportions of the different types of reinforcing fibers, their individual properties, the laminate architecture, and particularly on the steel fiber resin adhesion. So far, common constitutive laws for fiber reinforced composites have very limited suitability for the complex interrelation between the nonlinear plastic behavior of steel fibers and the elastic behavior of the carbon fibers. For this reason, a novel analytical method is developed to predict the failure performance of fiber hybrid composites. In principle, the analytical approach is based on a structural dynamic analysis of the fracture gap formation during failure and thus unloading of the brittle carbon fibers. The present paper covers the derivation of this analytical approach and its exemplary application to a steel and carbon fiber reinforced hybrid composite. A final comparison with an experimentally obtained stress–strain curve validates the theoretical model introduced. Abstract : The integration of ductile continuous steel fibers into thermoset carbon fiber reinforced polymer enables significant enhancements of its damage tolerance and crashworthiness. As shown in previous studies, this post damage performance depends on many different influences and need to be better understood. For this reason, a novel analytical approach is presented and exemplary applied to a steel and carbon fiber reinforced hybrid composite.